2002
DOI: 10.1007/s00424-002-0881-2
|View full text |Cite
|
Sign up to set email alerts
|

ATP-induced internalization of amphibian epithelial P2X receptors is linked to channel opening

Abstract: A family of ATP-gated, non-selective cation channels known as P2X receptors are involved in purinergic synaptic transmission and other, as yet poorly defined, functions. After repeated exposure to ATP some of these channels no longer respond, a phenomenon known as run-down. In some P2X receptor subtypes, run-down has been associated with endocytosis. Recently, we have cloned a P2X receptor from larval amphibian skin (fP2X5) that shows profound run-down. To visualize the receptor in the plasma membrane of Xenop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The Ca 2+ i -and cAMPindependent effect of ATP that we ascribe to P2X stimulation was brief, indicating little importance in regulation of epithelial ion transport. The short duration of the P2X response may be due to an internalization of the receptor after binding of the agonist [19]. Thus, the small, initial, positive spike in I sc in response to ATP (Fig.…”
Section: Purinergic Regulation Of Ion Transportmentioning
confidence: 96%
“…The Ca 2+ i -and cAMPindependent effect of ATP that we ascribe to P2X stimulation was brief, indicating little importance in regulation of epithelial ion transport. The short duration of the P2X response may be due to an internalization of the receptor after binding of the agonist [19]. Thus, the small, initial, positive spike in I sc in response to ATP (Fig.…”
Section: Purinergic Regulation Of Ion Transportmentioning
confidence: 96%
“…The N-terminal phosphorylation of P2X receptors may, on the one hand, enhance the rate of desensitization and thereby also modulate the peak current amplitude [P2X 2 (Boue-Grabot et al, 2000)], and, on the other hand, it may decrease the membrane expression of this receptor by interfering with its internalization [P2X 5 (Jensik and Thomas, 2002)]. It has been hypothesized that the completely conserved PKC phosphorylation site of the P2X 3 signaling peptide within the subsequence 1-44 is essential to pass the endoplasmatic reticulum or the plasma membrane (Mager et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…PKC1 does not interact with other peptide modules, but is a part of the signalling peptide (fragment 1 -44, the cleavage site is between position 44 and 45). The T18 of P2X5 is homologous with the T12 of P2X3 and it was shown that the T18A mutant blocks P2X5 internalisation and did not show ATP-activated currents [24]. For personal use only.…”
Section: Internalisationmentioning
confidence: 98%
“…In homology to the results of other proteins, it may be speculated that an agonist-promoted downregulation of P2X receptors [23][24][25][26][27][28] is also related to certain N-glycosylation sites. The N-glycosylation site (Asn187) of the β 2 -adrenergic receptor contributes to the internalisation during a long-term agonist exposure and the mutant Asn187Asp failed to display long-term agonist-promoted downregulation [29].…”
Section: Internalisationmentioning
confidence: 99%